Pengaruh Kompetensi Pedagogik dan Kompetensi Kepribadian Dosen terhadap Kedisiplinan Belajar Statistika Mahasiswa Perbankan Syariah Institut Agama Islam Darussalam - Nawal Ika Susanti (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
This study aims to determine whether or not there is an influence of pedagogic competence and lecturer's personality competence on the statistical learning discipline of Islamic Banking students and to determine the best model formed in this study. This study took a sample of 36 respondents, with data collection using a questionnaire instrument. Before obtaining objective data, the instrument used was tested for validity using the Pearson correlation formula, reliability with the Cronbach Alpha formula, and data normality with the Kolmogorov Smirnov test. The research data were analyzed using descriptive quantitative statistical techniques, with multiple regression analysis and linearity test. The results of testing the research hypothesis show that there is no influence of pedagogic competence on the discipline of studying statistics, there is an influence of personality competence on the discipline of studying statistics of Islamic Banking students. The discipline of studying statistics is influenced by the pedagogic competence and personality competence of the lecturers by 25.6%, while the remaining 74.4% is influenced by variables outside the study. The best model that is formed is the second model, namely the model of the lecturer's personality competence variable on the statistical learning discipline of Islamic Banking students